An Indirect Colorimetric Method for Potassium Determination in Soil Using a Paper Device and Smartphone - Thinikan Thongkam; Khuanjit Hemavibool (Molekul, 2022)
This study presents a simple method for determination of potassium in microliter scale using a paper device together with a smartphone. The method begins with the ion-pair extraction of dibenzo-18-crown-6-K+ complex into dichloromethane with an excess amount of calmagite. The aqueous phase containing the remaining calmagite is transferred to the paper device, where a smartphone is used to capture the color and convert to RGB value. The linear detection range was found to cover potassium concentrations from 20 mg L-1 to 120 mg L-1. The detection and quantification are 5.41 mg L-1 and 18.03 mg L-1, respectively. Potassium detection was carried out in a variety of actual soil samples, and the results were validated against spectrophotometric results using a paired t-test, which indicated high accuracy. The proposed method is simple, fast, and inexpensive, and it requires no complicated equipment, making it ideally suited for detection of potassium in soil.